2020
DOI: 10.3897/ap.2.e1369
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Risks of Using the Digital Educational Environment

Abstract: The article describes the digitalization stages of secondary and higher education in the Russian Federation and considers the main risks that may be caused by this trend. Among the health risks, there are disorders of the musculoskeletal system, impaired brain development, nervous strain and sleep problems, skin and respiratory diseases. The following communicative risks prevail: the risk of weakening motivation to learn, empathy, leadership skills. The main risks in the field of information security are the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 1 publication
0
10
0
2
Order By: Relevance
“…According to a survey (Kuznetsova and Azhmukhamedov, 2020), the digital educational space can be dangerous in terms of negative impact on the physical health of participants in the learning process (for example, musculoskeletal system, brain, skin, respiratory system, cardiovascular system, etc. ), as well as their psycho-emotional state (increased nervous tension, sleep disturbances, irritability) and cause risks that can be attributed to social (in particular, reduced motivation to learn).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a survey (Kuznetsova and Azhmukhamedov, 2020), the digital educational space can be dangerous in terms of negative impact on the physical health of participants in the learning process (for example, musculoskeletal system, brain, skin, respiratory system, cardiovascular system, etc. ), as well as their psycho-emotional state (increased nervous tension, sleep disturbances, irritability) and cause risks that can be attributed to social (in particular, reduced motivation to learn).…”
Section: Resultsmentioning
confidence: 99%
“…Despite a number of risks posed by the use of the digital learning environment, surveys (Kuznetsova and Azhmukhamedov, 2020) showed that 90% of respondents consider digital education a promising alternative to traditional one, and 64% believe that the digital learning environment has a positive impact on learning outcomes. Kamahina et al (2019) conducted a survey of teachers to determine their readiness to effectively use the digital educational space in the educational process, which showed that more than 90% of respondents use digital tools in the educational process, such as electronic textbooks, digital educational environments and online services.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the risks of Using the Digital Educational Environment, Kuznetsova and Azhmukhamedov (2020) analyze the stages of secondary and higher education's digitization in the Russian Federation and conclude that disorders of the musculoskeletal system, decreased brain development, nervous exhaustion and sleep issues, skin and respiratory ailments are just a few of the health dangers that are directly related to the use of digital tools in schools. In addition to this, Kuznetsova and Azhmukhamedov (2020) also concluded that the health and SOR are the highest ones, a result which perfectly aligns to the results of our research.…”
Section: Discussionmentioning
confidence: 99%
“…In the specialized literature, risks are found under various dimensions, but for our research, we considered four categories as essential in digital pedagogy. The most relevant risks for our analysis are as follows: SER (Di Gioia et al, 2019;Baeva, 2021;Crepax et al, 2022), SOR (Kuznetsova and Azhmukhamedov, 2020;Sorokoumova et al, 2021), OBR (Bencsik et al, 2022) and HER (Kuznetsova and Azhmukhamedov, 2020; Ma ˛kosa, 2013) (see Appendix).…”
Section: Scalesmentioning
confidence: 99%
“…On the other hand, digitalization is regarded as an attack on human culture. There are too many educational risks causing dehumanization of people and substitution of real values with imaginary ones [5,6,7].…”
Section: Introductionmentioning
confidence: 99%